Estudio comparativo de la modalidad de trabajo implementada en el Departamento de Desarrollo Comunitario del GAD Chone durante la emergencia sanitaria 2020 - Mendoza Cedeño, María Gabriela (2021)
The purpose of this research was to carry out a comparative study of the work modality between the administrative and operations personnel of the social area of the GAD in Chone during the 2020 health emergency, to determine the work performance of the employees. It began with the observation and identification of the different work modalities applied, later the work performance achieved by the studied personnel was measured, to then establish the advantages and disadvantages of the work modalities adopted in the Department of Community Development. The used methods were: inductive, deductive, descriptive, analytical and synthetic; techniques such as the interview, carried out with the director and the coordinators of this direction; on the other hand, the survey was applied to public servants, obtaining relevant information for this study from both techniques that allowed conclusions to be drawn about the work modalities applied in the operational personnel of the coordination of culture, heritage and sport, establishing an affectation since the programmed projects were not fully executed, with few students who managed to complete the courses, thus low performance is evident. For this reason, it is necessary to direct guidelines that ensure the adoption of modalities that efficiently respond to the activities carried out within the aforementioned coordination, as well as the fulfillment of institutional goals.